Is the role of cultural capital in student achievement in South Korea different? A systematic review. Issue 6 (18th August 2019) - Choi, Yeonsoo; Kim, Sung won; Hong, Won-Pyo
ABSTRACT: Empirical studies focused on cultural capital only emerged since the 2000s in South Korea. This article is the first to conduct a systematic review aiming to shed light on how the theory of cultural capital has been applied in South Korea. Our main goal is to understand: how the cultural capital–students' achievement association in South Korea differs from research in western industrialized contexts; and how cultural capital has been defined, and which dimensions have been highlighted as core elements of social reproduction in South Korea. Based on an examination of both quantitative and qualitative studies published since 2000, our analysis suggests that, contrary to the focus on the highbrow culture or classed-based parenting practices in western literature, the institutionalized striving for upward social mobility through education and a popular desire to acquire globally convertible cultural capital is key to unpacking the notion of cultural capital in the South Korean context.